2019
DOI: 10.3390/app9091865
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study and Optimization of the Organic Rankine Cycle with Pure NovecTM649 and Zeotropic Mixture NovecTM649/HFE7000 as Working Fluid

Abstract: The Organic Rankine Cycle (ORC) is widely used in industry to recover low-grade heat. Recently, some research on the ORC has focused on micro power production with new low global warming potential (GWP) replacement working fluids. However, few experimental tests have investigated the real performance level of this system in comparison with the ORC using classical fluids. This study concerns the experimental analysis and comparison of a compact (0.25 m3) Organic Rankine Cycle installation using as working fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…The turbine isentropic efficiency varies with the operating conditions, and its values are based on the experimental data provided by the manufacturer ENOGIA [27]. In particular, under nominal operating conditions, the maximum isentropic efficiency is about 0.53, and it decreases with a pressure ratio, as better detailed in [28]. For the sake of the present analysis, a gear pump was considered to ensure the required refrigerant mass flow rate.…”
Section: The Models Of the Main Subsystemsmentioning
confidence: 99%
“…The turbine isentropic efficiency varies with the operating conditions, and its values are based on the experimental data provided by the manufacturer ENOGIA [27]. In particular, under nominal operating conditions, the maximum isentropic efficiency is about 0.53, and it decreases with a pressure ratio, as better detailed in [28]. For the sake of the present analysis, a gear pump was considered to ensure the required refrigerant mass flow rate.…”
Section: The Models Of the Main Subsystemsmentioning
confidence: 99%
“…The ORCs have been studied extensively in the past decades. Several studies have evaluated working fluids (WFs) and ORC system configurations from a thermo-economic perspective (Imran et al, 2018;Blondel et al, 2019;Anastasovski et al, 2020). Mudasar et al (2017) studied a biogas-fueled high-temperature ORC (HT-ORC) system using toluene as the WF and reported that the maximum power generated and thermal efficiency were 156 kW and 19%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A di↵erent power generation technology is therefore investigated here, that of a partial admission action turbo-expander. The fact that in this type of expander all the expansion takes place in the distributor should limit the influence of leaking losses and guarantee a good level of work output [14]. However, due to the intrinsic behavior of the machine, special attention must be paid to the interdependence between the physics governing the expander and the cycle in which it is integrated.…”
Section: Introductionmentioning
confidence: 99%